2019
DOI: 10.21314/jop.2019.230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of enterprise risk management on the performance of companies in transition countries: Serbia case study

Abstract: The market position of a company influences its performance. In hazard conditions, all the factors that determine a company's market position and business are exposed to risk. An effective program of enterprise risk management (ERM) decreases the level of risk and improves company performance. ERM is a process that identifies and evaluates all potential losses that can occur in business organizations and selects techniques that can handle and prevent such losses in accordance with the requirements of Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Several studies have found that the ERM has a significant effect on the financial performance of companies (Shad and Lai 2019;Liem 2018;Olayinka et al 2017;Soliman and Adam 2017). Another approach has focused on operational performance and ERM (Altanashat et al 2019;Callahan and Soileau 2017;Panić et al 2019). According to Dey et al (2018), there is a significant association between the degree of financial risk disclosure and a firm's financial characteristics as a function of firm size, financial performance and auditor.…”
Section: Erm and Firm Performancementioning
confidence: 99%
“…Several studies have found that the ERM has a significant effect on the financial performance of companies (Shad and Lai 2019;Liem 2018;Olayinka et al 2017;Soliman and Adam 2017). Another approach has focused on operational performance and ERM (Altanashat et al 2019;Callahan and Soileau 2017;Panić et al 2019). According to Dey et al (2018), there is a significant association between the degree of financial risk disclosure and a firm's financial characteristics as a function of firm size, financial performance and auditor.…”
Section: Erm and Firm Performancementioning
confidence: 99%
“…In the face of increasingly complex competition in the market environment, the financial risk management of enterprises is under increasing pressure. Literature [16] explains that enterprise risk management has the role of reducing the company's operating risks and improving the company's economic efficiency, and cites seven risky operations of the company as a framework for building an enterprise risk management analytical framework, in order to make clear what kind of impacts different types of enterprise risks have on the operation of the company and market competition. Literature [17] explored the association between operational capability and sustainable risk management in Palestinian insurance firms and pointed out that the strength of ERM capability significantly affects the profitability of firms.…”
Section: Introductionmentioning
confidence: 99%
“…Effective risk management is essential in a very unpredictable business environment to ensure a company's survival and success (Bartram, 2000;Virglerova et al, 2022). As a result, many organizations use Enterprise Risk Management (ERM) to assess every possible risk and determine how much of an impact they may have on the company's value (Meulbroek, 2005;Hoyt & Liebenberg, 2011;Panić et al, 2019).…”
Section: Introductionmentioning
confidence: 99%